International Political Economy: The Struggle for Power and Wealth - Thomas D. Lairson; D. Skidmore (United States: Harcourt Brace College Publishers, 1997)
This edition of "International Political Economy: The Struggle for Power and Wealth" carries over many of the objectives and themes central to the first edition, while also addressing a number of new topics and issues.
(NP(B/16918s
Keywords: world economy -- globalization -- trade and development